2022
DOI: 10.3390/ijerph192215083
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Food Consumption, Dietary Quality, and Dietary Intake of Adolescents in Saudi Arabia

Abstract: High fast-food consumption is a common public-health concern among adolescents, due to its link to a number of non-communicable diseases. Frequent consumption of fast food may also affect diets of individuals; however, research addressing this issue is lacking in Saudi Arabia. We aimed to investigate the association between fast-food consumption, dietary quality, and dietary intake of adolescents in Saudi Arabia. This is a cross-sectional study of 617 healthy adolescents aged 11–18 years, who were recruited ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…However, since the focus of the study was more on the biochemical aspect of osteomalacia, only biomarkers of impaired mineralization were studied. Recent investigations on the dietary intake of children and adolescents in Saudi Arabia reported that almost a third of adolescents frequently (≥2 times per week) consume fast food [36] and children under 12 years have an above-average intake of cholesterol and saturated fat [37], reflecting high consumption of fast food. Furthermore, local dairy products in Saudi Arabia which are considered good sources of vitamin D and calcium for the younger population contain substantially lower amounts of these micronutrients when compared to fortified products imported from the United States [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, since the focus of the study was more on the biochemical aspect of osteomalacia, only biomarkers of impaired mineralization were studied. Recent investigations on the dietary intake of children and adolescents in Saudi Arabia reported that almost a third of adolescents frequently (≥2 times per week) consume fast food [36] and children under 12 years have an above-average intake of cholesterol and saturated fat [37], reflecting high consumption of fast food. Furthermore, local dairy products in Saudi Arabia which are considered good sources of vitamin D and calcium for the younger population contain substantially lower amounts of these micronutrients when compared to fortified products imported from the United States [38].…”
Section: Discussionmentioning
confidence: 99%
“…Most school food service supervisors in the investigated schools were not trained in nutrition, yet they were responsible for ordering food and creating meal plans (31). Multiple studies (26,37,38) confirmed these results by revealing that Saudi adolescents have poor dietary practices and food preferences. Of the 1,133 high school students surveyed, only 27.7% ate breakfast daily on average.…”
Section: Primary Caregiver Both Parents)mentioning
confidence: 90%
“…Even more concerning, only almost three-fifths of adolescents (35.7%) and slightly more than a quarter (28.6%) said they ate vegetables and fruits every day. Also, more adolescents (37.1%) reported drinking fizzy beverages every day ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tool has been modified and used among different populations, including adolescents in Saudi Arabia. [21][22][23][24] The SFFFQ included the following foods: (1) "Fruits"; (2) "Fruit juice"; (3) "Salad"; (4) "Cooked vegetables"; (5) "Fried potatoes/chips"; (6) "Beans or legumes"; (7) "Fiber-rich breakfast cereal"; (8) "Whole wheat bread"; (9) "Cheese/Yoghurt"; (10) "Crisps/Savory snacks"; (11) "Sweet biscuits"; (12) "Ice cream/cream"; (13) "Fizzy drinks/ Pop"; (14) "Beef or lamb"; (15) "Chicken or turkey"; ( 16) "Processed meats/meat product"; (17) "Processed chicken/turkey"; (18) "Fried white fish"; (19) "White fish"; (20) "Oily fish". Food frequencies for items 1-13 were: "Never or Rarely"; "<1 time per week"; "1 time per week"; "2-3 times per week"; "4-6 times per week"; "1-2 times per day"; "3-4 times per day"; "≥ 5 times per day".…”
Section: Assessment Of Media Usementioning
confidence: 99%